1990
DOI: 10.1021/bi00498a002
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of aflatoxin B1 in two oligodeoxynucleotide adducts: comparative proton NMR analysis of d(ATCAFBGAT).cntdot.d(ATCGAT) and d(ATAFBGCAT)2

Abstract: 8,9-Dihydro-8-(N7-guanyl-[d(ATCGAT)])-9-hydroxyaflatoxin B1.d(ATCGAT) and 8,9-dihydro-8-(N7-guanyl-[d(ATGCAT)])-9-hydroxyaflatoxin B1.8,9-dihydro-8-(N7-guanyl-[d(ATGCAT)])-9-hydroxyaflatoxin B1 were prepared by direct addition of afltoxin B1 8,9-epoxide to d(ATCGAT)2 and d(ATGCAT)2, respectively. In contrast to reaction of aflatoxin B1 8,9-epoxide with d(ATCGAT)2 which exhibits a limiting stoichiometry of 1:1 aflatoxin B1:d(ATCGAT)2 [Gopalakrishnan, S., Stone, M. P., & Harris, T. M. (1989) J. Am. Chem. Soc. 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
123
1
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(141 citation statements)
references
References 43 publications
14
123
1
3
Order By: Relevance
“…The observed mutational asymmetry disposed to the 5' side of the adduct is in accord with the molecular architecture of AFB1-N7-Gua established by NMR (40) showing the aflatoxin moiety of the adduct intercalated on the 5' face of guanine (Fig. 4).…”
Section: Discussionsupporting
confidence: 83%
“…The observed mutational asymmetry disposed to the 5' side of the adduct is in accord with the molecular architecture of AFB1-N7-Gua established by NMR (40) showing the aflatoxin moiety of the adduct intercalated on the 5' face of guanine (Fig. 4).…”
Section: Discussionsupporting
confidence: 83%
“…Although both AFB 1 -N7-Gua and AFB 1 -FAPY adducts intercalate at the 5Ј face of the modified base in duplex DNA (37,38), potentially explaining the similar mutation spectrum, with predominant mutation being G to T transversion, it does not provide insight for the differential mutagenic potential between these two lesions (Table 1) (20). Recently, crystallographic studies revealed that the conformation of the AFB 1 moiety within the active site of the archaea polymerase Dpo4 differed between AFB 1 -N7-Gua and AFB 1 -FAPY due to the distinct orientations of the N7-C8 bond of AFB 1 -N7-Gua as compared with the N 5 -C8 bond of AFB 1 -FAPY (26).…”
Section: Discussionmentioning
confidence: 99%
“…Among these AFB1-DNA adducts, 8,9-di-hydro-8-(N 7 -guanyl)-9-hydroxy-AFB1 (AFB1-N 7 -Gua) adduct is the most common type identified and confirmed in vivo researches (19, 25-27, 29, 30). The formation of this adduct proceeds by a precovalent intercalation complex between double-stranded DNA and the highly electrophilic, unstable AFB1-epoxide isomer (31,32). After that, the induction of a positive charge on the imidazole portion of the formed AFB1-N 7 -Gua adduct gives rise to another important a DNA adduct, a ring-opened formamidopyridine AFB1 (AFB1-FAPy) adduct (33,34).…”
Section: Afb1 Exposure and Dna Damage And Repairmentioning
confidence: 99%